2000
DOI: 10.1002/1097-0290(20000820)69:4<359::aid-bit2>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical manipulation of hepatocyte aggregation can selectively induce or repress liver-specific function

Abstract: Controlled activation of hepatocyte aggregation is critical to three‐dimensional (3D) multicellular morphogenesis during native regeneration of liver as well as tissue reconstruction therapies. In this work, we quantify the stimulatory effects of two model hepatotrophic activators, epidermal growth factor (EGF) and hepatocyte growth factor (HGF), on the aggregation kinetics and liver‐specific function of hepatocytes cultured on organotypic substrates with differing mechanical resistivity. Substrate‐specific mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 38 publications
4
87
0
1
Order By: Relevance
“…In the present work, we have extended these characterizations by showing that culture in an appropriate 3D environment led to a strong apico-basolateral polarization and the maintenance of liver-specific functions such as a high level of albumin secretion and accumulation of bilirubin. In agreement with previous reports on long-term culture of primary hepatocytes (LeCluyse et al, 1996;Moghe et al, 1996;Semler and Moghe, 2001;Semler et al, 2000), we found that the microenvironment of the Matrigel basalmembrane extract provided the best spatial and biochemical cues for mhAT3F polarization and function. It is noteworthy that Matrigel's chemical composition is similar both to the basal-membrane components of the liver in vivo (Stamatoglou and Hughes, 1994) and to the endogenous matrix deposited by aggregates of primary liver cells in suspension culture (Landry et al, 1985).…”
Section: Nf-κb Regulates the Apoptotic Response To Deathreceptor Stimsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present work, we have extended these characterizations by showing that culture in an appropriate 3D environment led to a strong apico-basolateral polarization and the maintenance of liver-specific functions such as a high level of albumin secretion and accumulation of bilirubin. In agreement with previous reports on long-term culture of primary hepatocytes (LeCluyse et al, 1996;Moghe et al, 1996;Semler and Moghe, 2001;Semler et al, 2000), we found that the microenvironment of the Matrigel basalmembrane extract provided the best spatial and biochemical cues for mhAT3F polarization and function. It is noteworthy that Matrigel's chemical composition is similar both to the basal-membrane components of the liver in vivo (Stamatoglou and Hughes, 1994) and to the endogenous matrix deposited by aggregates of primary liver cells in suspension culture (Landry et al, 1985).…”
Section: Nf-κb Regulates the Apoptotic Response To Deathreceptor Stimsupporting
confidence: 93%
“…Thus, hepatocytes in polarized, functional organoids modulate an intracellular signal transduction pathway, allowing the recapitulation of their physiological response to an apoptotic stimulus. membrane extracellular matrix, provides an especially appropriate environment for hepatocyte culture, as judged by the cells' morphology and metabolism (LeCluyse et al, 1996;Semler and Moghe, 2001;Semler et al, 2000). Interestingly, in addition to the chemical composition of the matrix, the physical properties of the gels (especially the pore size and the pliability) profoundly influence both the spatial organization and the differentiation of the cells (Moghe et al, 1996;Ranucci et al, 2000;Semler and Moghe, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the biomaterials employed have unmatched mechanical properties to the infarcted myocardium. The stiffness of a range of possible injectable materials is in the range of 10 Pa to 20 kPa, such as fibrin (50 Pa), 224 Matrigel (30-120 Pa), 225 type I collagen gels (20-80 Pa for 1-3 mg/mL), 226 bioactive hydrogels based on N-isopropylacrylamide (100-400 Pa), 227,228 alginate (100 Pa to 6 kPa), 229 and PEG (1-3 kPa). 230 These biomaterials are significantly softer than the human cardiac muscle at the end of diastole, the stiffness of which is 50 kPa in normal hearts or 200-300 kPa in congestive heart-failure hearts.…”
Section: Limitations Of An Injectable Systemmentioning
confidence: 99%
“…There was a lag time before steady increase in cell number on the e-BC gel. Semler et al reported that cells shows high growth rate on matrices with high mechanical compliance such as TCP, whereas the cells aggregate three-dimensionally on matrices with low mechanical compliance such as collagen gel [39]. Therefore, the difference in the mechanical properties of the surface of the culture substrate might affect the initial rate of cell growth.…”
Section: Biological Properties Of E-bc Gelmentioning
confidence: 99%